1996
DOI: 10.1111/j.1475-097x.1996.tb00565.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac output and blood pressure during active and passive standing

Abstract: The present study compared the haemodynamic pattern of active and passive standing. We used non-invasive techniques with beat-to-beat evaluation of blood pressure, heart rate and stroke volume. Seven healthy subjects, aged 24-41 (mean 30) years were examined. Finger blood pressure was continuously recorded by volume clamp technique (Finapres), and simultaneous beat-to-beat beat stroke volume was obtained, using an ultrasound Doppler technique, from the product of the valvular area and the aortic flow velocity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
69
3
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 24 publications
8
69
3
1
Order By: Relevance
“…Tanaka et al (62) and Sprangers et al (59) also observed a decrease of total peripheral RI and MAP during postural transitions due to vasodilation and movement of blood to the lower body. The decrease of total peripheral RI was greater in men and could be due to greater leg muscle mass (55) and/or a greater number of dilated vessels.…”
Section: Discussionmentioning
confidence: 90%
“…Tanaka et al (62) and Sprangers et al (59) also observed a decrease of total peripheral RI and MAP during postural transitions due to vasodilation and movement of blood to the lower body. The decrease of total peripheral RI was greater in men and could be due to greater leg muscle mass (55) and/or a greater number of dilated vessels.…”
Section: Discussionmentioning
confidence: 90%
“…This was interpreted as an indication of translocation of blood to the thorax. The greater BP reduction in the initial phase of active standing may reflect systemic vasodilatation caused by activation of cardiopulmonary baroreflexes; this is probably due to a rapid shift of blood from the splanchnic vessels in addition to the shift from muscular vessels associated with abdominal and calf muscle contraction [24]. At least similar, and probably even amplified, changes may be expected during the shift from squatting to standing.…”
Section: Changes From Squatting To Standingmentioning
confidence: 91%
“…Therefore, the homoeostatic mechanisms are the same, but with different quantity of the same time-dependent quality. A carefully performed study compared haemodynamic changes during active standing and following passive 60° tilt in young healthy subjects [24]. BP and HR were continuously recorded by a Finapres ® , and simultaneous beat-to-beat stroke volume was obtained using an ultrasound Doppler technique.…”
Section: Changes From Squatting To Standingmentioning
confidence: 99%
“…Further by Rossberg and Penaz and Krediet and Wieling added that on standing and loss of compression of the legs, there would be an immediate reduction in leg vascular resistance due to already existing locally mediated vasodilatation. [26][27][28][29] Moreover, also supported by studies by Tschakovsky and Sheriff as the muscular effort involved in standing up from a squat position is considerable, it has been demonstrated that rapid vasodilatory mechanisms act in proportion to contraction intensity. [30] This would be expected to cause further vasodilatation.…”
Section: Discussionmentioning
confidence: 70%